Biallelic variants in CEP164 cause a motile ciliopathy‐like syndrome. Issue 3 (3rd November 2022) - Devlin, Laura A.; Coles, Janice; Jackson, Claire L.; Barroso‐Gil, Miguel; Green, Ben; Walker, Woolf T.; Thomas, N. Simon; Thompson, James; Rock, Simon A.; Neatu, Ruxandra; Powell, Laura; Molinari, Elisa; et al.
Abstract: Ciliopathies may be classed as primary or motile depending on the underlying ciliary defect and are usually considered distinct clinical entities. Primary ciliopathies are associated with multisystem syndromes typically affecting the brain, kidney, and eye, as well as other organ systems such as the liver, skeleton, auditory system, and metabolism. Motile ciliopathies are a heterogenous group of disorders with defects in specialised motile ciliated tissues found within the lung, brain, and reproductive system, and are associated with primary ciliary dyskinesia, bronchiectasis, infertility and rarely hydrocephalus. Primary and motile cilia share defined core ultra‐structures with an overlapping proteome, and human disease phenotypes can reflect both primary and motile ciliopathies. CEP164 encodes a centrosomal distal appendage protein vital for primary ciliogenesis. Human CEP164 mutations are typically described in patients with nephronophthisis‐related primary ciliopathies but have also been implicated in motile ciliary dysfunction. Here we describe a patient with an atypical motile ciliopathy phenotype and biallelic CEP164 variants. This work provides further evidence that CEP164 mutations can contribute to both primary and motile ciliopathy syndromes, supporting their functional and clinical overlap, and informs the investigation and management of CEP164 ciliopathy patients. Abstract :